Increasing Children's Religious Values Through Method of Storying Stories of Islamic Figures in Group B Children - Triyani (Yayasan Sinergi Kawula Muda, 2025)
This research aimed to determine whether the method of telling the stories of Islamic figures could increase the value of religiosity in group B at TK Aisyiyah Bustanul Athfal Tombiobong. The subjects in this study are group B children of Aisyiyah Bustanul Athfal Kindergarten aged 5-6 years, totaling 10 students, consisting of 3 male students and seven female students. This is a classroom action research that was carried out in two cycles. Each cycle consists of two meetings. Each cycle of learning activities consists of 4 stages: planning, implementing, observing, and reflecting. The data collection techniques in this study are observation sheets, interviews, and documentation. The data analysis technique uses descriptive analysis, which is both quantitative and qualitative. The overall assessment of students during the pre-action with three aspects, knowing God through his creation, getting used to worship, and behaving politely and politely, shows the average value of children's religiosity in the developing category (MB) 44.2%. Then in the first cycle of the first meeting, the average value of children's religiosity in the starting to develop (MB) category was 50%. In cycle I of the second meeting, the value of children's religiosity was developing according to expectations (BSH) 63.27%. At the first meeting of cycle II, it was still in the developing category as expected (BSH) at 72.5%. Then at the second meeting of cycle II, it became very well developed (BSB) at 84.2%. There was an increase from pre-action to cycle I of 19.07 and from cycle I to cycle II an increase of 20.93%. Based on the research above, it can be concluded that the method of telling stories of Islamic figures can be used to increase the religiosity value of children in group B at Aisyiyah Bustanul Athfal Tombiobong Kindergarten.